NIR-light triggered dual-cascade targeting core-shell nanoparticles enhanced photodynamic therapy and immunotherapy. (December 2021) - Wei, Dengshuai; Chen, Youbai; Huang, Yun; Li, Peng; Zhao, Yao; Zhang, Xianghong; Wan, Jia; Yin, Xiangye; Liu, Tang; Yin, Jiye; Liu, Zhaoqian; Zhang, Qi; et al.
Highlights: Aggregation induced emission (AIE) monomer (7 ) with two hydroxyl groups was synthesized. Polymers with either ROS generation or cell and organelle targeting ability were synthesized. Dual-cascade targeting (DCT) of cell and organelle nanoparticles with high spatiotemporal precision were developed. A strategy to maximize the effectiveness of combined photodynamic and immunotherapy were provided. Graphical Abstract: ga1 Abstract: Cell and organelle targeting of nanomedicines are two cascade processes that lead to drug internalization and subsequent enrichment on the final target. However, it is still challenging to achieve dual-cascade targeting (DCT) with high spatiotemporal precision and efficiency via sequential activation of nanomedicine. Herein, we developed DCT core-shell nanoparticles triggered by near infrared (NIR) light for optimized photodynamic therapy (PDT) and immunotherapy. To obtain the DCT core-shell nanoparticles, an aggregation induced emission (AIE) monomer (7 ) with two hydroxyl groups was first synthesized. Thereafter, two core polymers with either reactive oxygen species (ROS) generation or mitochondrial targeting ability, and a shell polymer with cell surface targeting were synthesized. Assembly of the core polymers and subsequent coating with the shell polymer formed DCT core-shell nanoparticles (NP4). After NP4 were i.v. injected into mice, they were efficiently accumulated at tumor sites. Upon NIR light irradiation, NP4 induced robust ROS generation with concomitant detachment of negative shell polymers with polyethylene glycol (PEG), resulting in charge reversal and the positively charged core nanoparticles for mitochondrial targeting. Subsequently, ROS generated in mitochondria upon continuous light irradiation killed cancer cells via PDT. In addition, PDT induced immunogenic cell death (ICD), thus activating adaptive immunity. This work provided a novel strategy for nanoparticles with DCT capacity to maximize the effectiveness of combined photodynamic and immunotherapy.